Edible wild plants and insects in Western Friuli local Knowledge (Friuli Venezia Giulia, Italy). - DREON A. L.; PAOLETTI, MAURIZIO (Museo di Berna, 2009)
ABSTRA CT Contrib. Nat. Hist. 12: 461–488. Folk traditional diets in Western Friuli include wild plants and few invertebrates (i.e. insects) that are peculiar in the Southern Alps. 156 plants are listed here, ranging from 200 m to 2200 m a.s.l. This selection is the result of the research of 64 informants who contributed with their personal experiences. Recovery of scattered knowledge is valuable for maintaining and sustaining its use and enhancing a wild biodiversity base for agroecology, conservation and ecotourism. Pistiç, frita and lidùm are some of the names used for about 50–60 herbs collected in field margins, hay meadows, woodlands and the wild, most commonly in spring. In order to be consumed, most herbs are boiled together and are later sautéed with butter or lard and garlic. The higher range pre-alpine Carnic slopes have supported seasonal sheep and cow grazing and summer pastoral communities have traditionally used plants as well for salads, soups and spices in addition to the boiled-sautéed dish. Furthermore, herbs have been used as medicinal elixirs and for milk processing. For instance, Lycopodium annotinum L. was employed to filter milk; Asplenium ruta-muraria L. was cooked with maize flour to prepare "fregole" a dish eaten with milk or coffee made from barley. Specifically, collections of these useful alpine plants include: Chenopodium bonus-henricus L., Aruncus dioicus (Walter) Fernald, Cicerbita alpina (L.) Wallr., Rumex alpinus L., Carlina acaulis L., Myrrhis odorata (L.) Scop., Ranunculus hybridus Biria (dry leaves used as pepper), and raw bulbils of Polygonum viviparum L. Some parts or products of insects were also eaten in these summer meadow areas ("magredi") and hay meadows such as the ingluvies of adult Lepidoptera (Zygaenidae Zygaena spp. and Ctenuchidae Syntomis spp.). Bees such as Bombus sp. were exploited for honey content in their ingluvies and their nests were exploited for honey. The pollen and nectar deposits of Osmia sp. inside snail shells were eaten as a snack. Of the ...